Oxygen scavengers for food packaging applications: A review. (August 2019) - Dey, Aishee; Neogi, Sudarsan
Abstract: Background: Many food products available are sensitive to oxygen and which upon prolonged exposure may lead to deterioration in the food quality like change in taste, odour and colour of the food or facilitate the growth of microorganisms in them. Addition of oxygen scavengers is one of the means to reduce the oxygen exposure on food products. Oxygen scavengers are a type of active packaging technique which absorb the dissolved oxygen or oxygen in the headspace leading to extended shelf life and retainment of the original food quality. Scope and approach: Extensive work has been done in this particular field. In this review, oxygen scavenging systems like iron, palladium, ascorbic acid, tocopherol, unsaturated hydrocarbons, microorganisms have been thoroughly discussed along with their applicability with respect to the moisture content of the targeted food products. The mechanism of action of the respective systems are also explained adequately. Key findings and conclusion: Many naturally occurring oxygen scavengers based on phenolic compounds and naturally occurring minerals like hydrotalcite have been mentioned in this review which have not yet been investigated thoroughly. Not much research has been done on zero valent metals like copper etc as oxygen scavenger. Highlights: Oxygen degrades food by rapid oxidation of fats, lipids present in food and enhancing the growth of microorganisms. Oxygen scavenging is an active packaging technique used for increasing shelf life of the pacakaged foods. Commonly used oxygen scavengers like iron, platinum group metals, unsaturated hydrocarbons, ascorbic acids, α-tocopherol, enzymes and microorganisms have been discussed. The most widely accepted mechanisms for each type of oxygen scavengers have been discussed. Commercially available oxygen scavengers have been reported.